Cobalt Compounds and Applications 2019
DOI: 10.5772/intechopen.85773
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Single Atom Heterogeneous Catalyst: Method of Preparation, Characterization, Catalysis, and Mechanism

Abstract: Transition metal nanoparticles and metal oxide have been used extensively for a wide range of applications in electrochemical reactions (HER, ORR, OER) and energy storage (supercapacitors batteries). To make less expensive, the use of transition metal at minimum metal contents without compromising the catalytic activity could be one way. Most of the catalytic process takes place on the surface and reaction dynamic can be manipulated by changing the particle size and shape. For a long time, single metal atom or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The catalysts show a promising performance, in which no loss of catalytic activity in electrochemical reactions is observed (Figure 4I). Undeniably, improving the interaction between a metal atom and a host is believed to be the right answer for stabilising the SACs on a catalyst support or host matrix [64], and this can also be achieved by functionalizing with suitable "anchor" groups such as carboxyl, hydroxyl, and amide groups [65,66].…”
Section: Mutual Metal-support Interactionmentioning
confidence: 99%
“…The catalysts show a promising performance, in which no loss of catalytic activity in electrochemical reactions is observed (Figure 4I). Undeniably, improving the interaction between a metal atom and a host is believed to be the right answer for stabilising the SACs on a catalyst support or host matrix [64], and this can also be achieved by functionalizing with suitable "anchor" groups such as carboxyl, hydroxyl, and amide groups [65,66].…”
Section: Mutual Metal-support Interactionmentioning
confidence: 99%
“…These unique structural and electronic properties of carbon nanomaterials make them promising supports for synthesizing stable CUS metal atoms . Several recent studies have demonstrated the use of graphene, graphene oxide, and N-doped graphene for the preparation of SA CUS. ,,,, , However, metal atoms on nonfunctionalized carbon supports can be mobile under operational conditions rendering them unstable during catalysis . Therefore, insertion of anchoring groups such as N (pyridinic or pyrrolic nitrogen) in the carbon matrix is one possible way to stabilize CUS catalytic sites .…”
Section: Introductionmentioning
confidence: 99%